Manifestations of body care and fashion beauty in Andalusian heritage - lanani, meriama (The Algerian Historical Journal, 2026)
The study of the topic of body care and fashion beauty in Andalusian society is a hitorical study that requires the research to exploit various historical texts that can provide information about the interest of the Andalusian individual in good beauty and uniform. Following a series of texts, the research concluded that Andalusian society is the most caring society of hygiene, eating good and paying attention to the beauty of indulgence and decorating it, taking into account the choice of suitable costumes and clothing as seasons and occasions, as well as the use of clothing and coordination in wearing them . This, if anything, demonstrates the cultural upliftment of Andalusian society.